THE QUALITY OF ELECTRICITY IN TRACTION NETWORK FOR THE DC ELECTRIC LOCOMOTIVES PANTOGRAPHS - Mishchenko, T. M. (Science and Transport Progress, 2008)
The numerical estimation of the electric energy quality parameters of voltage on a current collector of the DC electric rolling stock is executed.